Self-confidence, Overconfidence and Prenatal Testosterone Exposure: Evidence from the Lab - Dalton, Patricio S.; Ghosal, Sayantan (Frontiers in Behavioral Neuroscience, 2018)
This paper examines whether foetal testosterone exposure predicts the extent of confidence and over-confidence in own absolute ability in adulthood. To study this question, we elicited incentive-compatible measures of confidence and over-confidence in the laboratory and correlate them with measures of right hand 2D:4D, used as as a marker for the strength of prenatal testosterone exposure. We provide evidence that men with higher prenatal testosterone exposure (i.e. low 2D:4D ratio) are less likely to set unrealistically high expectations about their own performance. This in turn helps them to gain higher monetary rewards. Men exposed to low prenatal testosterone levels, instead, set unrealistically high expectations which results in self-defeating behavior..